Thoughtful Labor. Simone Weil on Vocational Education - Zuurmond , Anouk (Labyrinth, 2023)
The work of Simone Weil is increasingly important in the field of philosophy of education, however, her ideas on schooling have been largely understood from her later, religiously inspired works. This paper argues that this approach does not do justice to the fact that Weil's thinking about education is already present in her earlier works and that her educational ideas were profoundly inspired by her experience as a factory worker. One of the key insights Weil gained whilst working in a factory was the importance of what she refers to as "thoughtful labor". This paper addresses this concept by engaging with the earlier work of Weil on educational philosophy. Furthermore, these ideas are juxtaposed with a German tradition in pedagogical thinking, emerging around the same time, on the notion of Berufsbildung, which indicates a combination of professional, personal and societal formation in vocational training. I argue that Weil shares with this tradition the crucial idea that work can have an educational value, and that it should be integrated into the educational system. However, the tradition of Berufsbildung has been critiqued for its strong tendency to consolidate existing power structures; I suggest that this critique is still valid on current discourses on general formation and Bildung in vocational education. In the final part of this article, I argue that on this point the work of Simone Weil differs from the notion of Berufsbildung, as she stands in a tradition of educational thinkers who remind us of the potential revolutionary character of education.